TINDAK PIDANA PENCUCIAN UANG HASIL DARI KORUPSI YANG MENDAPAT PENGAMPUNAN PAJAK - Yuni Priskila Ginting (Fakultas Hukum Universitas Pasundan, 2020)
Taxpayers who participate in the tax amnesty program, provided that they should declare complete data and information on their assets, and clearly settled for taxation purposes, will not be subjected to any administrative sanctions and tax penalties. The tax amnesty law can neither prevent the disclosure of the data and information on the origin of the properties nor the origin of the reported money. Declared is in the form of data and information on assets, which originates from legal and illegal activities. This paper discusses assets resulting from the crime of money laundering, which can still be investigated and confiscated by the state, based on the law on money laundering and the law on corruption, even though asset data has been included in the tax amnesty. In principle, criminal sanctions cannot be abolished, just because they have paid taxes, or just because they have received tax amnesty.The results of the research in this paper are that the concept of tax amnesty law, money laundering and corruption requires the application of digitalization technology with the aim of expanding a taxation database that is valid, comprehensive, and integrated with an online system in order to force taxpayers to comply with taxes. , which will improve voluntary tax compliance for all taxpayers and for taxpayers who perpetrate money laundering in particular.So it is necessary to make a law that regulates tax penalties from replacement money which is calculated based on the present value of the perpetrator of the crime of laundering who has permanent (inkracht). Keywords: money laundering, corruption, tax, assessable, tax amnesty.